2022
DOI: 10.1021/acs.iecr.1c03645
|View full text |Cite
|
Sign up to set email alerts
|

Tubular Clay Nano-Straws in Ordered Mesoporous Particles Create Hierarchical Porosities Leading to Improved CO2 Uptake

Abstract: The use of solid adsorbents for CO2 capture is of importance in the development of technologies to remove this greenhouse gas. High surface area mesoporous materials are used to encapsulate or functionalize amines that selectively capture CO2. The MCM-41 class of hexagonally ordered mesoporous silicas have surface areas between 1000 and 1500 m2/g, which in principle allows a significant degree of capture when amines such as polyethyleneimine (PEI) are encapsulated within the pores and occupy the entire surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
(89 reference statements)
0
6
0
Order By: Relevance
“…Therefore, it can be concluded that the HNT-supported catalyst has substrate selectivity for p -xylene thanks to its tubular structure with Ru particles embedded into the tubes, providing o - and m -xylenes with lower diffusivity and acting as nanoreactors. 27,35 Similar to the composite-based analogue, no isomerization or acid-catalyzed cracking was observed over the HNT-supported Ru catalyst, which is proved by the n -heptane content being constant over the whole temperature range.…”
Section: Resultsmentioning
confidence: 82%
“…Therefore, it can be concluded that the HNT-supported catalyst has substrate selectivity for p -xylene thanks to its tubular structure with Ru particles embedded into the tubes, providing o - and m -xylenes with lower diffusivity and acting as nanoreactors. 27,35 Similar to the composite-based analogue, no isomerization or acid-catalyzed cracking was observed over the HNT-supported Ru catalyst, which is proved by the n -heptane content being constant over the whole temperature range.…”
Section: Resultsmentioning
confidence: 82%
“…We also note that the introduction of APTES leads to small changes in peak position, which we attribute to the inclusion of Si atoms from APTES that results in a small but perhaps not negligible contribution to the X-ray scattering. This shows that the incorporation of HNT as straws into MCM-41 did not alter the mesoporous MCM-41 framework. , Upon amine functionalization, the intensity of the (100) peak decreases as the weight of APTES increases and the secondary peaks lose resolution. This can be attributed to the attached APTES chain within the silica framework. The presence of silicon and oxygen in the organic APTES molecules increases the electron density of MCM-41 and M40H after amine functionalization.…”
Section: Results and Discussionmentioning
confidence: 84%
“…We introduce HNT into MCM-41 as “nanostraws” with the hypothesis that the large pores of HNT will facilitate the entry of amines to the interior and thus improve amine loading. In our earlier work, we studied class I type systems of encapsulating polyethylenimine (PEI) and showed that the introduction of HNT into MCM-41 improved PEI loading by 40% and doubled CO 2 capture efficiencies . In this study, we extend this concept of improved access to the particle interior through the nanostraws to enhance the covalent grafting of APTES into the MCM-41 matrix and develop an improved class II adsorbent with higher CO 2 capture.…”
Section: Introductionmentioning
confidence: 99%
“…4 . 25 After spray-drying, separated microparticles were collected and calcined at 550 °C to remove organics ( Fig. 4a ).…”
Section: Hybridization Of Clay Nanotube Systems With Synthetic Mesosi...mentioning
confidence: 99%
“…The surface area could be moderately increased by alumina acid etching or drastically enhanced by selective adherence of smaller-pore silica, such as MCM-41 (Mobil Composite Material-41) or nanocarbon (Scheme 1, bottom right). 8,[23][24][25][26] Negatively charged nanotube outer surfaces were modied with cationic surfactants, e.g. quaternary ammonium salts such as cetyltrimethyl ammonium bromide.…”
Section: Introductionmentioning
confidence: 99%